Factors Affecting the Adsorption of Zn and Cd Ions from Aqueous Solution onto Vermiculite - Wu Xiaofu; Zhao Fang; Chen Mingli; Zhang Yangli; Zhao Chong; Zhou Hailan (Adsorption Science & Technology)
Experiments were conducted to investigate the influence of different factors on the adsorption of Zn 2+ and Cd 2+ ions from aqueous solution onto vermiculite. The ratio of the initial concentration of ions, C 0 , to the adsorbent concentration, W 0 , was shown to be the key factor determining the equilibrium ion adsorption density, q e . Subject to the magnitude of C 0 /W 0 , the value of q e could either attain its maximum level, q m (the maximum adsorption density), when the solid surface was fully saturated, or approach its critical limit, q c (the C 0 /W 0 ratio), when the ions in the bulk solution had been completely removed. The main mechanism for adsorption in the systems studied was ion-exchange. An increase in Zn 2+ or Cd 2+ ion adsorption from the single metal ion solution resulted in an increase in the concentrations of unadsorbed K + , Na + , Ca 2+ and Mg 2+ ions remaining in the bulk solution. Competition between adsorbing ions was observed in the mixed K + –Zn 2+ –Cd 2+ ion system. Although temperature had a positive effect upon the adsorption of Zn 2+ and Cd 2+ ions, its effect was statistically negligible over the range 15–45°C. The negative effect of decreasing pH values on the adsorption process was only significant below a pH value of 4.0, indicating that the adsorption of Zn 2+ and Cd 2+ ions would be significantly depressed when high amounts of H + ions are present in the system.